Designing for Impact: Tools for Reducing Disparities in Health. (2nd July 2018) - Phillips, Brian; Katz, Deb
Abstract : Our living environments can play a crucial part in our health – physical, emotional and psychological. But these impacts cannot be so easily and quickly measured or anticipated as, say, build costs or energy efficiency. How, then, can architects ensure that the housing they design will be health enhancing? Philadelphia‐based architectural practice Interface Studio Architects (ISA) has been developing tools for this purpose through a range of recent projects, public and private. The firm's principalsBrian Phillips and Deb Katz describe the resulting strategies that are encouraging physical activity, nurturing residents' sense of wellbeing and inviting wider neighbourhood interaction for greater health equity.